Changing human–nature relationships: Insights from Guinea‐Bissau woodlands - Ana Leite; Luís Catarino; Sambu Seck; Quintino Mbunhe; Aida Cuní‐Sanchez (People and Nature)
Abstract The ecological impacts of landscape changes resulting in significant simplification of natural systems have been extensively studied worldwide. Yet, few studies have examined how such biophysical changes affect the value local communities place on nature and their relationships with it. In this study, we delve into the case of Guinea‐Bissau, where woodland cover has been increasingly replaced by commercial cashew plantations. Using a sociocultural valuation approach, our empirical research provides a comprehensive assessment of the woodlands' contributions to local communities as well as the potential disruptions caused by the ongoing biophysical changes on the woodlands. We focused on 20 villages of four different ethnic groups—Manjack, Balanta, Mandinka and Fulani—and used a combination of focus group discussions and walks‐in‐the‐woods. The study's participants identified 19 nature's contributions to people from the woodlands, which revealed a combination of instrumental, relational and intrinsic values in ways that reflect their subsistence needs and social–cultural contexts. We also found that these values are being impacted, mostly negatively, by the ongoing biophysical changes in the ‘natural’ landscapes tied to regional and global dynamics. Moreover, our study reveals that local communities are aware of ongoing biophysical changes in their woodlands and perceive them as having negative ecological and psychological consequences for them. Synthesis and applications: Our study highlights the significance of using a sociocultural perspective to investigate how changes in the landscape affect local peoples' values of nature and their relationships with it. This information can help shape policies and management decisions towards creating better futures that are meaningful for both humans and non‐humans. Read the free Plain Language Summary for this article on the Journal blog.